Locally advanced breast cancer: breast-conserving surgery and other factors linked to overall survival after neoadjuvant treatment - Nobrega, Gabriela Bezerra; Mota, Bruna Salani; de Freitas, Gabriela Boufelli; Maesaka, Jonathan Yugo; Mota, Rosa Maria Salani; Goncalves, Rodrigo; Trinconi, Angela Francisca; Ricci, Marcos Desidério; Piato, José Roberto; Soares-Jr, José Maria; Baracat, Edmund Chada; Filassi, José Roberto (Frontiers in Oncology, 2023)
Abstract Background: Recent data suggests that breast-conserving surgery (BCS) may positively impact overall survival (OS) in early breast cancer. However, the role of BCS in locally advanced breast cancer (LABC) following neoadjuvant therapy (NAT) remains uncertain. Methods: We conducted a retrospective cohort study involving 530 LABC patients who underwent surgery after NAT between 2010 and 2015. Outcomes examined included OS, distant recurrence rates (DRR), and loco-regional recurrence rates (LRR). Results: Among the 927 breast cancer patients who received NAT, 530 were eligible for our study. Of these, 24.6% underwent BCS, while 75.4% underwent mastectomy (MS). The median follow-up duration was 79 months. BCS patients exhibited a higher pathological complete response (PCR) rate compared to those who underwent MS (22.3% vs. 10%, p < 0.001). The 6-year OS rates for BCS and MS were 81.5% and 62%, respectively (p < 0.000). In multivariate OS analysis, MS was associated with worse outcomes (OR 1.678; 95% CI 1.069–2.635; p = 0.024), as was body mass index (BMI) (OR 1.031; 95% CI 1.006–1.058; p = 0.017), and staging IIIB or IIIC (OR 2.450; 95% CI 1.561–3.846; p < 0.000). Conversely, PCR (OR 0.42; 95% CI 0.220–0.801; p = 0.008) was associated with improved survival. DRR was significantly lower in BCS (15.4%) compared to MS (36.8%) (OR 0.298; 95% CI 0.177–0.504). LRR were comparable between BCS (9.2%) and MS (9.5%) (OR 0.693; 95% CI 0.347–1.383). Conclusion: Our findings suggest that BCS is oncologically safe, even for patients with large lesions, and is associated with superior OS rates compared to MS. Additionally, lower BMI, lower pretreatment stage, and achieving PCR were associated with improved survival outcomes.